ВТРАТИ ЕЛЕКТРОЕНЕРГІЇ, ВИКЛИКАНІ ПЕРЕТОКАМИ ВІДНОВЛЮВАНИХ ДЖЕРЕЛ ЕНЕРГІЇ, В БАЛАНСІ ЕЛЕКТРИЧНИХ МЕРЕЖ - Лежнюк, П.Д.; Гунько, І.О.; Козачук, О.І.; Лисий, В.М. (Інститут електродинаміки НАН України, Київ, 2023)
Renewable energy sources (RES) affect the technical and economic parameters of electrical grids. In particular, with the increase in the amount of electricity in the EPS balance produced by RES, it is relevant to determine the power and electricity losses in electric grids caused by flows of electricity from RES. The method, algorithm and program for determining the component of power and electricity losses from RES in the total losses of electrical grids have been developed. The basis of the method is a mathematical model of the electrical grid for determining losses, which uses the current distribution coefficients in the circuits of the circuits from RES nodes and node voltages. As a result, a matrix of power loss distribution coefficients is formed in the branches of the circuit depending on the power in the nodes of the circuit. The voltages during the formation of the loss distribution matrix are determined based on the results of the calculation of steady-state modes of the electrical network or according to experimental measurement data. It is shown that the values of electricity losses in electrical grids caused by RES can be used during the operational planning of the electricity balance in the EPS and, since they are addressable, their cost can be compensated accordingly. References 8, figures 2.